Chiral Squaramide Catalyzed Asymmetric Conjugate Additions of 3-Substituted Oxindoles to Vinylphosphonates - Duan, Shu-Wen; Liu, Yi-Yin; Ding, Wei; Li, Tian-Ren; Shi, De-Qing; Chen, Jia-Rong; Xiao, Wen-Jing (Synthesis, 2013)
An efficient organocatalytic enantioselective conjugate addition of 3-substituted oxindoles to activated vinylphosphonates has been described. This reaction allows the facile synthesis of a new family of organophosphorus derivatives bearing an oxindole motif in high chemical yields with good to excellent stereoselectivities.
Keywords: organophosphorus compounds; conjugate addition; oxindole; organocatalysis; squaramide catalyst